As tecnologias digitais de comunicação e informação: influencias e possibilidades para um novo entendimento da expressão da religiosidade na atualidade - Brito, Reginaldo de Souza (2014)
The goal of this work is to analyze the development of the mass communication processes beginning with the advent of Internet and how these new instruments of amplification of communication influence the religious mobility in Brazil. It is also to verify the new communicational possibilities and possibilities of religious expression and experience based on the virtual environments. In a first moment religious mobility and changes in the religious field will be dealt with as well as their relation with the new communicability broadened by the current mass media. After this we will verify the possibility of new constructions and possibilities of understanding, access to information and religious practices based on the digital environment as well as the greater possibility of new personalized configurations of intertwined religiosity. Finally some of the existing experiences of expressions of religiosity and religious practices will be presented based on the digital interface which has already been used by some officially Christian denominations and other non-Christian ones with the goal of analyzing these experiences and their influence, assimilation, comprehension and dissemination of faiths.